»Speaking of Job«: A Philological and Exegetical Proposal on Job 42:7–8 - Rogland, Max F. (Zeitschrift für die alttestamentliche Wissenschaft, 2024)
This study proposes a new analysis and translation of Job 42:7-8, focusing on the renderings of the prepositions אל and כ. Understood correctly, these verses indicate that the three friends have spoken falsely, not about God, but Job. In this way they have borne false testimony about Job to God, and it is for this reason that his wrath is kindled against them.